An anode buffer layer with size-controlled Ag nanoparticles for polymer solar cells with improved efficiencies1. Issue 21 (6th March 2015) - Ganeshan, Dhanavel; Chen, Shan-Ci; Yin, Zhigang; Zheng, Qingdong
<x xml:space="preserve">Abstract</x> The PCE of the best performing PSC was enhanced to 9.45% by incorporating 55 nm Ag NPs in the PEDOT:PSS.